2018
DOI: 10.1186/s12885-017-3967-0
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment of resectable biliary tract cancer with cisplatin plus gemcitabine: A prospective single center phase II study

Abstract: BackgroundBiliary tract cancer (BTC) is a dismal disease, even after curative intent surgery. We conducted this prospective, non-randomized phase II study to evaluate the feasibility and efficacy of cisplatin and gemcitabine as adjuvant treatment in patients with resected BTC.MethodsPatients initially received gemcitabine 1000 mg/m2 alone on days 1, 8 and 15 every 28-days for a total of six cycles (single agent cohort), and after protocol amendment a combination therapy with gemcitabine 1000 mg/m2 and cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…e current chemotherapeutic drugs used in gallbladder cancer include platinum, gemcitabine, fluorouracil, etc. [9,10]. HIPEC has achieved unique effects in the treatment of peritoneal cancer (PC).…”
Section: Discussionmentioning
confidence: 99%
“…e current chemotherapeutic drugs used in gallbladder cancer include platinum, gemcitabine, fluorouracil, etc. [9,10]. HIPEC has achieved unique effects in the treatment of peritoneal cancer (PC).…”
Section: Discussionmentioning
confidence: 99%
“…Some report showed the benefit of disease-free survival (39), but the evidence is insufficient due to the small number (<10) of 5-year survivors and retrospective study (38). Moreover, some reports have revealed the effectiveness of chemotherapy for biliary tract cancer (40). However, adjuvant chemotherapy for biliary tract cancer has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies are needed. A large multi-national study (ACTICCA-1) is evaluating the combination of gemcitabine plus cisplatin for adjuvant chemotherapy with results expected within the next years (40,43).…”
Section: Discussionmentioning
confidence: 99%
“…Given that GEM/CDDP has been the standard firstline treatment for patients with unresectable biliary tract carcinoma as indicated in the ABC-02 trial (7), GEM/ CDDP should be effective as adjuvant chemotherapy as well. A non-randomized small cohort phase II study indicated the promising survival of patients undergoing curative resection for biliary tract carcinoma (43). Moreover, a multicenter, open-label, randomized phase III trial on the efficacy of adjuvant GEM/CDDP is underway (44).…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%